FORMATION OF INFORMATION AND DATA SERVICE COMPETENCE AMONG PROGRAMMERS (Web of Teachers: Inderscience Research, 2025)
This article examines both the content and the practical significance of cultivating information and data service (IDS) competence among prospective programmers. It emphasizes that modern software products, databases, and online platforms, as well as information security issues, remain critically important components of the digital environment in which programmers operate. Within this context, the article explores contemporary demands for effectively integrating IDS competence into the professional practice of programmers and discusses potential methods for doing so.